EPIDEMIOLOGICAL INVESTIGATION OF NOMA IN PAPUA PROVINCE IN 2017 - Asrul Kaimudin; Atik Choirul Hidajah (Universitas Airlangga, 2020)
Background: Indonesia Ministry of Health in October 2017 obtained information from the Public Health Emergency Operation Center (PHEOC) that there allegations of noma case in a toddler from the Korowai tribe in Asmat District. Purpose: This study aims to describe the magnitude of the noma problem, identify risk factors, and find other noma cases for prevention and control. Methods: This was a descriptive study using a case study approach. Primary data was obtained from interviews with family or close relatives of patients to obtain information about patient identity, medical history, and risk factors. Measurement of nutritional status and oral health was done by measuring weight or height and checking their oral health. Secondary data was obtained from Asmat District health office (Dinkeskab Asmat) and Yaniruma Health Center. The data analyzed were geographical, demographic, socio-cultural, transportation, and communication condition. Results: Noma sufferer was a 5-years-old child who lived in Afimabul village. There was not other cases of Noma found in Korowai tribal community. A long distance to reach health services and no availability of communication tools to Korowai tribe in Afimabul village made them inaccessible. The results of the identification of risk factors in 46 children found that the majority of them had low oral hygiene (73.91%) and consumed uncooked water (80.43%). Besides, some had an index of thin body weight (15.22%), and very lean (6.52%), and also found the suspected measles. Conclusion: There was only one case found in the Asmat district. Moreover, there were still found Korowai children with thin and very lean nutritional status and suspected measles who are risk factors for noma.